Studi Literatur: Prediksi Kata Berikutnya dengan Metode Recurrent Neural Network - Trigreisian, Alwizain Almas; Harani, Nisa Hanum (Universitas Samudra, 2024)
Next-word prediction is one of the most frequently used tasks in natural language processing. The Recurrent Neural Network (RNN) method is one method that has been proven to be effective in predicting the next word in a sentence, as it is capable of processing text data with order and context. In this research, various algorithms used in the development of next word prediction using the RNN method were analyzed. Some of these algorithms include LSTM (Long Short-Term Memory) and bidirectional LSTM. The results of this research show that the use of the RNN method in predicting the next word is able to provide better results compared to other methods. However, there are still some challenges that need to be overcome in developing the RNN model to predict the next word. Therefore, further research needs to be done in overcoming these challenges so that the use of the RNN method can be further optimized in predicting the next word in a sentence.